Differentiating fulminant EBV infection complicated by HLH from Lymphoma: report of a case and a brief literature review - Bradley Zehr; Kristina Brannock; Rebecca Wyma; Samir B. Kahwash (BMC, 2023)
Abstract Epstein-Barr virus (EBV) infection may present with fulminant constitutional symptoms, cytopenia(s), and systemic lymphadenopathy, raising clinical suspicion for lymphoma and prompting lymph node and bone marrow biopsies. At the microscopic level, the histopathologic findings in cases of acute EBV lymphadenitis may mimic certain lymphoid neoplasms, creating a range of differential diagnoses and diagnostic pitfalls. We present a case of fulminant EBV infection in an adolescent whose clinical and radiographic findings led to lymph node and bone marrow biopsies to rule out lymphoma. One week after being diagnosed with acute EBV infection (infectious mononucleosis), a 17-year-old Caucasian male presented with worsening symptoms including persistent fever, progressive, painful lymphadenopathy, and splenomegaly. A peripheral blood smear showed lymphocytosis with many reactive lymphocytes, anemia, and thrombocytopenia. Laboratory studies showed elevated ferritin, triglycerides, and soluble IL-2/CD25. A cervical lymph node biopsy demonstrated an EBV-positive, reactive B-immunoblast proliferation with large atypical lymphoid cells mimicking Reed-Sternberg cells of Hodgkin lymphoma, in addition to patchy vasculitis, coagulative necrosis, and prominent hemophagocytic activity. Bilateral bone marrow biopsies showed a hypercellular marrow with patchy infiltrates of similar EBV-positive, large atypical lymphoid cells, as well as prominent hemophagocytic activity. The diagnosis of acute EBV associated lymphoproliferation with concurrent hemophagocytic lymphohistiocytosis (HLH) was rendered. Recognition of common and uncommon clinical presentations of acute EBV infection is essential, particularly when histopathologic findings raise suspicion for a possible hematolymphoid neoplasm. Both the lymph node architectural and viral cytopathic changes observed in EBV lymphadenitis exhibit significant morphologic overlap with classic Hodgkin lymphoma (cHL) and several other lymphomas, including anaplastic large cell lymphoma, diffuse large B cell lymphoma, and angioimmunoblastic T cell lymphoma. Recognition of immunohistochemical staining patterns in EBV lymphadenitis is critical to avoid misdiagnosis. Conversely, bona fide lymphoma, particularly cHL, can masquerade as EBV infection. We provide a concise discussion and tables of the histopathologic differential diagnosis of EBV lymphadenitis, including cHL and other lymphomas. Pathologists should include acute EBV infection within the differential diagnosis when confronted with clinical and pathologic findings concerning for lymphoma, particularly in adolescents and young adults.